Assessment of energy and nutrient intake of sri lankan mothers with prior gestational diabetes mellitus at 6-week postpartum: A community-based study - Thamudi Darshi Sundarapperuma; Sudharshani Wasalathanthri; Priyadarshika Hettiarachchi; Champa Jayalakshmie Wijesinghe (Wolters Kluwer Medknow Publications, 2023)
Background: Gestational diabetes mellitus (GDM) is one of the leading causes for the future diabetes. Diet modification is an imperative part in attenuating this progression. Objectives: This study assessed energy and nutrient intakes of Sri Lankan mothers at 6 weeks after delivery, with the aim of developing specific dietary guidelines for postpartum mothers with GDM. Materials and Methods: A community-based, descriptive cross-sectional survey was conducted as a part of a quasi-experimental study. Nutrient and energy intakes were assessed among 100 mothers using 24-h dietary recall and a validated food frequency questionnaire. Energy and nutrient intakes were analyzed using NutriSurvey 2007 (EBISpro, Germany) which was modified for native food recipes and food composition tables for Sri Lanka. Results: The mean ± standard deviation intakes of total calories, carbohydrate, protein, and fat were 2817 ± 984 kcal, 445 ± 186 g, 95 ± 39 g, and 87 ± 58 g, respectively. The total calorie intake was significantly higher when compared to recommended levels based on the body mass index in both normal weight (3033 ± 1122 vs. 2300 kcal/d; P < 0.00) and overweight or obese (2759 ± 944 vs. 1800 kcal/d; P < 0.00) postpartum women. In the obese group, daily carbohydrate, fat, and protein intakes were significantly higher than the recommended values (P < 0.00). Folic acid intake was lower in both normal (23.7 vs. 400; P < 0.001) and obese or overweight (63 vs. 400; P < 0.001) groups. Conclusion: The study indicated that in majority of the mothers with GDM, the daily calorie and carbohydrate intakes were higher than the recommended. The findings suggest the need for developing a scientifically feasible and culturally acceptable dietary modification program. All macronutrients were taken more than the recommended amounts, especially in the overweight/obese group.